Posterior cingulate cortex downregulation training using fMRI neurofeedback in adolescents with early life adversity exposure: a randomized, single-blind trial - Xiaoqian Yu; Aki Tsuchiyagaito; Masaya Misaki; Gabe Cochran; Zsofia P. Cohen; Manpreet K. Singh; Martin P. Paulus; Robin L. Aupperle; Namik Kirlic (Translational Psychiatry)
Abstract Early life adversity (ELA) disrupts default mode network (DMN) integrity subserving self-referential processes involved in emotional awareness and regulation. Mindfulness training (MT) reduces self-referential processing and down-regulates the DMN. We employed neurofeedback-augmented mindfulness training (NAMT), combining a core mindfulness strategy (focusing on breath) with real-time fMRI neurofeedback (rtfMRI-nf) to modulate DMN by targeting the posterior cingulate cortex (PCC). ELA-exposed (ELA; n = 43) and healthy control (HC; n = 40) adolescents completed a scan with three conditions: (a) Focus-on-breath (MT): rtfMRI-nf was presented as a variable-height bar, and adolescents attempted to lower the bar; (b) Describe: engaging self-referential processing; and (c) Rest. ELA were single-blind randomized to active PCC rtfMR-nf (NF; n = 22) or artificial feedback (SHAM; n = 21). Adolescents reported perceived stress, state mindfulness, and affect at baseline, post-training, and one-week follow-up. General linear models (GLMs) examined group differences (ELA vs. HC; NF vs. SHAM) on neural (MT vs. Describe) and self-report measures. ELA showed greater difficulty in PCC down-regulation relative to HC. For ELA, SHAM evidenced similar PCC down-regulation as active NF. All adolescents reported increased state mindfulness post-training. Relative to HC, ELA reported greater improvements in positive affect, negative affect and stress at follow-up. There was no difference in self-reported measures between active and SHAM. PCC responses in ELA confirm the region’s utility as a potential treatment target. NAMT was feasible and acceptable for ELA-exposed adolescents, but may not enhance mindfulness training more than SHAM. Optimal strategies for enhancing PCC regulation in ELA may be elucidated with future research.